Kinetically competing huntingtin aggregation pathways control amyloid polymorphism and properties - Jayaraman, Murali (2012)
In polyglutamine (polyQ) containing fragments of the Huntington’s disease protein huntingtin (htt), the N-terminal 17 amino acid htt(NT) segment serves as the core of α-helical oligomers whose reversible assembly locally concentrates the polyQ segments, thereby facilitating polyQ amyloid nucleation. A variety of aggregation inhibitors have been described that achieve their effects by neutralizing this concentrating function of the htt(NT) segment. In this paper we characterize the nature and limits of this inhibition for three means of suppressing htt(NT)-mediated aggregation. We show that the previously described action of htt(NT) peptide-based inhibitors is solely due to their ability to suppress the htt(NT)-mediated aggregation pathway. That is, under htt(NT) inhibition, nucleation of polyQ amyloid formation by a previously described alternative nucleation mechanism proceeds unabated and transiently dominates the aggregation process. Removal of the bulk of the htt(NT) segment by proteolysis or mutagenesis also blocks the htt(NT)-mediated pathway, allowing the alternative nucleation pathway to dominate. In contrast, the previously described immunoglobulin-based inhibitor, the anti-htt(NT) V(L) 12.3 protein, effectively blocks both amyloid pathways, leading to stable accumulation of non-amyloid oligomers. These data show that the htt(NT)-dependent and independent pathways of amyloid nucleation in polyQ-containing htt fragments are in direct kinetic competition. The results illustrate how amyloid polymorphism depends on assembly mechanism and kinetics, and have implications for how the intracellular environment can influence aggregation pathways.